Meta-analytic review of online purchase intention: conceptualising the study variables - Munmun Ghosh (Cogent Business & Management, 2024)
This meta-analytic review conceptualises and synthesises the study factors related to this phenomenon to effectively comprehend online purchasing intention. This study's "online purchase intention" concerns consumers' propensity or likelihood to purchase via online channels. This review develops a conceptual framework that clarifies the aspects influencing online purchase intention by analysing pertinent data. The variables under investigation encompass usefulness, ease of use, congruence, trust, security, e-WOM and many other demographics and contextual factors. The potential moderators were also identified, and the moderating effect is validated in the study variable as framed in the conceptual framework. This review contributes to the field by offering valuable insights into the determinants of online purchase intention, enabling marketers and researchers to devise effective strategies to optimise consumer behaviour in the online shopping domain.
Keywords: 650; Online purchase intention; meta-analysis; consumer behaviour; technology; online